Legislative and judicial responses to workplace sexual harassment in mainland China: Progress and drawbacks - Wang, Hao (Frontiers in Public Health, 2022)
Background: China has recently upgraded its anti-sexual harassment laws and regulations. The first-ever Chinese Civil Code, which took effect in 2021, has explicitly defined sexual harassment and imposed affirmative duties on employers to prevent and correct work-related sexual harassment. This study aims to map the status quo of China’s anti-sexual harassment legal system and explore its progress and limits in dealing with workplace sexual harassment. Methods: We reviewed China’s anti-sexual harassment laws at the national, provincial, and municipal levels and observed how they were enforced in courts. All judicial cases of workplace sexual harassment published by Chinese courts between January 2021 and June 2022 were examined. From a comparative law perspective, we then identified the progress and drawbacks of China’s legislative and judicial responses to workplace sexual harassment. Results: China’s current anti-sexual harassment legal system, while have made commendable progress, has its drawbacks: the definition of sexual harassment remains to be clarified and expanded to make it clear that sexual harassment is a form of gender discrimination and can include hostile environment harassment that is not directed against a specific person; the employer’s obligations to prevent and correct sexual harassment need further delineation; employers lack guidelines for establishing a fair and effective grievance procedure; the difficulty of proving sexual harassment in litigation remains unsolved; the employer liability doctrine for sexual harassment lacks clarity; workers not in a traditional employment relationship receive inadequate legal protection from work-related sexual harassment. Conclusions: The issues mentioned above merit consideration in China’s future law revisions and judicial practice. In China and other societies where gender inequality remains high, it is recommended to regulate sexual harassment as a form of discrimination and to set clear compliance standards for employers in preventing and correcting sexual harassment.